Encyclopedia of the Bible and its reception - Helmer, Christine; McKenzie, Steven L.; Römer, Thomas; Schröter, Jens; Walfish, Barry Dov; Ziolkowski, Eric; Allison, Dale C.; Klauck, Hans-Josef; Furey, Constance M.; Matz, Brian J.; Gemeinhardt, Peter; LeMon, Joel M.; et al. (De Gruyter, 2009)
"EBR offers a comprehensive and in-depth rendering of the current state of knowledge on the origins and development of the Bible according to its different canonic forms in Judaism and Christianity. At the same time, EBR also documents the history of the Bible's reception in Judaism and Christianity as evident in exegetical literature, theological and philosophical writings of various genres, literature, liturgy, music, the visual arts, dance, and film, as well as in Islam and other religious traditions and contemporary movements."--Publisher's website
Verf.-Angabe anfangs: ed. by Hans-Josef Klauck ... - Danach ed. by Dale C. Allison ... - Später: ed. by Christine Helmer, Steven L. McKenzie, Thomas Römer, Jens Schröter, Barry Dov Walfish, Eric Ziolkowski. - Später: edited by Constance M. Furey, Peter Gemeinhardt, Joel M. LeMon, Thomas Römer, Jens Schröter, Barry Dov Walfish, Eric Ziolkowski. - Später: edited by Brennan Breed, Constance M. Furey, Peter Gemeinhardt, Joel M. LeMon, Thomas Römer, Jens Schröter, Barry Dov Walfish, Eric Ziolkowski
Keywords: Bible -- Encyclopedias; Bible -- Criticism, interpretation, etc -- History -- Encyclopedias; Bibel -- DNB; Wörterbuch; Exegese; Rezeption; Bibel